PENGARUH KARAKTERISTIK INDIVIDU, REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN DI PT. PETRO JAYA PUTRA - Anak Agung Dwi Widyani; Ni Made Satya Utami; Ida Ayu Mas Indah Primadani (VALUES, 2023)
This study aims to determine and analyze the influence of employee characteristics, reward and punishment on employee performance. This research was conducted at PT. Petro Jaya Putra which is located in West Denpasar. Data collection by distributing questionnaires with a Likert scale. The sample was determined using the census method, so that all 35 employees were used as the sample. The data analysis technique used is multiple linear regression analysis with the help of the SPSS 26.0 for windows program. Testing the data includes testing the validity with the Pearson product moment, testing the reliability using the alpha cronbanch value, then testing the classical assumptions before the regression analysis and testing the hypothesis with the t test and F test. The results of this study indicate that individual characteristics have a positive and significant effect on employee performance at PT. Petrojaya Putra. Reward has a positive and significant effect on employee performance at PT. Petrojaya Putra. Punishent has a positive and significant effect on employee performance at PT. Petrojaya Putra.